Synthesis and characterization of polymers based on citric acid and glycerol: Its application in non-biodegradable polymers (2015)
The notable increase in global consumption of plastics and their long residence time in the atmosphere show the great need for biodegradable products. In this project, we developed biodegradable polymers based on citric acid and glycerol. Their synthesis was carried out at different conditions of constant temperature and concentration and they were synthesized using an economically viable method. Characterization was undertaken using: Acid number, FTIR spectroscopy, refractive index, viscosity, impact analysis, tensile test, hardness, calorimetry, the % humidity (oven method with recirculating air), and density determination, along with qualitative evidence to corroborate their biodegradability. These elaborated polymers were mixed with medical grade PVC formulation, obtaining a hybrid polymer, showing their mechanical properties were changed.